Risk-Based Inspection Due to Corrosion Consequences for Oil and Gas Flowline: A Review - Mmahmood, Fatima; Jaafar , Dhifaf (Iraqi Journal of Chemical and Petroleum Engineering, 2022)
The petroleum industry, which is one of the pillars of the national economy, has the potential to generate vast wealth and employment possibilities. The transportation of petroleum products is complicated and changeable because of the hazards caused by the corrosion consequences. Hazardous chemical leaks caused by natural disasters may harm the environment, resulting in significant economic losses. It significantly threatens the aim for sustainable development. When a result, determining the likelihood of leakage and the potential for environmental harm, it becomes a top priority for decision-makers as they develop maintenance plans. This study aims to provide an in-depth understanding of the risks associated with oil and gas pipelines. It also tries to identify essential risk factors in flowline projects, as well as their likelihood and severity, in order to reduce loss of life and increased expenditures as a result of safety issues. The monetary quantification was used to determine the leakage-induced environmental losses. Using a 5-by-5 probability-currency matrix, the level of environmental risk was evaluated the safety and risk-based inspection (RBI) is evaluated through the use of specific schedules to determine the likelihood of failure (LOF) and Consequence of Failure (COF). The risk level appears in the matrix, and appropriate maintenance steps should be taken to reduce risks, such as injecting corrosion inhibitors to protect the Pipelines, activating cathodic protection or coating. Overall, this research contributes to the prevention of petroleum product leakage due to the corrosion consequences in the transportation sector. Also, encourage non-environmental risk decision-makers to gain a better understanding of the risk level.